2015
DOI: 10.3389/fpls.2015.00261
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances on the development and regulation of flower color in ornamental plants

Abstract: Flower color is one of the most important features of ornamental plants. Its development and regulation are influenced by many internal and external factors. Therefore, understanding the mechanism of color development and its regulation provides an important theoretical basis and premise for the cultivation and improvement of new color varieties of ornamental plants. This paper outlines the functions of petal tissue structure, as well as the distribution and type of pigments, especially anthocyanins, in color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
246
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(253 citation statements)
references
References 103 publications
(123 reference statements)
4
246
0
3
Order By: Relevance
“…In this study, we identified 10 TF families comprising 21 TF unigenes that represented potentially important regulators of anthocyanin biosynthesis in Lilium spp. The R2R3-MYB family plays a key role in regulating the spatiotemporal expression of anthocyanin biosynthetic genes in plants (Gonzalez et al, 2008; Zhao and Tao, 2015). This family is further classified into several subgroups, with the members of subgroup 6 positively regulating anthocyanin biosynthesis (Dubos et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified 10 TF families comprising 21 TF unigenes that represented potentially important regulators of anthocyanin biosynthesis in Lilium spp. The R2R3-MYB family plays a key role in regulating the spatiotemporal expression of anthocyanin biosynthetic genes in plants (Gonzalez et al, 2008; Zhao and Tao, 2015). This family is further classified into several subgroups, with the members of subgroup 6 positively regulating anthocyanin biosynthesis (Dubos et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…(Davies et al, 2012; Zhao and Tao, 2015). The anthocyanin biosynthetic pathway is one of the best-known specialized metabolic pathways and most of the anthocyanin biosynthetic genes have been characterized in different plant species (Winkel-Shirley, 2001; Grotewold, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Light is one of the important environmental factors that affect the anthocyanin biosynthesis [20]. Numerous studies have shown that light exposure can enhance the anthocyanin accumulation in fruit skin [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Flower colour is mainly decided by pigment, cell sap pH, metal elements, etc 3,. and the yellow petals are mainly related to flavonoids and carotenoids4.…”
mentioning
confidence: 99%